2006
DOI: 10.1176/appi.ajp.163.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Vardenafil in Men With Mild Depression and Erectile Dysfunction: The Depression-Related Improvement With Vardenafil for Erectile Response Study

Abstract: Vardenafil was well tolerated and highly efficacious in men with erectile dysfunction and untreated mild major depression. Significant improvements in erectile function and depression were observed in patients treated with vardenafil versus placebo. Erectile dysfunction treatment should be considered a component of therapy for men with depression and erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 21 publications
(26 reference statements)
3
43
2
2
Order By: Relevance
“…Finally, treatment of ED with phosphodiesterase 5 (PDE5) inhibitors has been shown to improve depressive symptoms in two randomized controlled trials. 22,23 It should be noted that the prevalence of depressive symptoms in our cohort was significantly higher than that found in epidemiological surveys. 5,6 In the Massachusetts Male Aging Study (MMAS) sample, the overall prevalence of depressive symptoms defined as CES-D416 was 12%, much lower than in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…Finally, treatment of ED with phosphodiesterase 5 (PDE5) inhibitors has been shown to improve depressive symptoms in two randomized controlled trials. 22,23 It should be noted that the prevalence of depressive symptoms in our cohort was significantly higher than that found in epidemiological surveys. 5,6 In the Massachusetts Male Aging Study (MMAS) sample, the overall prevalence of depressive symptoms defined as CES-D416 was 12%, much lower than in our study.…”
Section: Discussioncontrasting
confidence: 64%
“…The patient group treated with sildenafil citrate for ED for 12 weeks showed a remarkable improvement in their depression compared with the placebo control group. Rosen et al 32 who used verdenafil reported the same results. They argued that the result is powerful evidence showing the possibility that sexual dysfunction may be caused by depression.…”
Section: Discussionmentioning
confidence: 59%
“…Treatment of erectile dysfunction should be considered a component of therapy for men with depression and erectile dysfunction. 28 In our present study, the improvement of cognitive function may be closely linked to the improvement of depression and self-confidence, but there are different views on how cognitive dysfunction and depression are related. A classical viewpoint is that cognitive deficits are a net result of depression.…”
Section: Effect Of Repeated Dosing With Udenafil On Cognition Somatimentioning
confidence: 58%